Effect of calcination temperature on the surface morphology and crystallinity of tungsten (VI) oxide nanorods prepared using colloidal gas aphrons method - Abdullah S.F.; Radiman S.; Abd. Hamid M.A.; Ibrahim N.B. (Elsevier, 2023)
The effect of calcination temperature on the surface morphology and crystallinity of tungsten (VI) oxide, WO3 nanorods prepared using colloidal gas aphrons (CGAs) as template was studied. The synthesized WO3 nanorods were calcined in a furnace for 4 h at four different temperatures, i.e., 400, 500, 600 and 700 C. The morphology of the calcined WO3 nanorods have been characterized by both transmission electron microscope (TEM) and variable pressure scanning electron microscope (SEM) equipped with energy dispersive X-ray analysis (EDAX). The results showed that the calcination temperature influenced the shape and size of the WO3 nanorods produced. It is also found that the calcination at various temperature do not effect the composition and the purity of the WO3 nanorods. In order to characterize the crystalinity of WO3, X-ray diffraction (XRD) has been used. It shows that all the calcined WO3 produced are in crystalline form compared to the as-prepared WO3 nanorods, which is in amorphous form. 2006 Elsevier B.V. All rights reserved.